A High Fat Diet Increases Bone Marrow Adipose Tissue (MAT) But Does Not Alter Trabecular or Cortical Bone Mass in C57BL/6J Mice. Issue 9 (September 2015) - Doucette, Casey R.; Horowitz, Mark C.; Berry, Ryan; MacDougald, Ormond A.; Anunciado‐Koza, Rea; Koza, Robert A.; Rosen, Clifford J.
Abstract : Obesity has been associated with high bone mineral density (BMD) but a greater propensity to fracture. Some obese individuals have increased marrow adipose tissue (MAT), but the impact of MAT on bone turnover remains controversial, as do changes in BMD associated with a high fat diet (HFD). In this study we hypothesized that MAT volume would increase in response to HFD but would be independent of changes in BMD. Hence, we fed C57BL/6J (B6) male mice at 3 weeks of age either a high fat diet (60 kcal %) or regular diet (10 kcal %) for 12 weeks (n = 10/group). We measured MAT volume by osmium staining and micro‐CT (µCT) as well as bone parameters by µCT, histomorphometry, and dual‐energy X‐ray absorptiometry. We also performed a short‐term pilot study using 13‐week‐old B6 males and females fed a HFD (58 kcal %) for 2 weeks (n = 3/sex). Both long‐ and short‐term HFD feedings were associated with high MAT volume, however, femoral trabecular bone volume fraction (BV/TV), bone formation rate and cortical bone mass were not altered in the long‐term study. In the short‐term pilot study, areal BMD was unchanged after 2 weeks of HFD. We conclude that, for B6 mice fed a HFD starting at wean or 13 weeks of age, MAT increases whereas bone mass is not altered. More studies are needed to define the mechanism responsible for the rapid storage of energy in the marrow and its distinction from other adipose depots. J. Cell. Physiol. 230: 2032–2037, 2015. © 2015 Wiley Periodicals, Inc.